Role of intravenous immunoglobulin in the treatment of acute relapses of neuromyelitis optica: experience in 10 patients. (April 2014) - Elsone, Liene; Panicker, Jay; Mutch, Kerry; Boggild, Mike; Appleton, Richard; Jacob, Anu
Prompt treatment of neuromyelitis optica (NMO) relapses with steroids or plasma exchange (PLEX) often prevents irreversible disability. The objective of this study is to report the use of intravenous immunoglobulins (IVIG) as treatment for acute relapses in NMO. A retrospective review of 10 patients treated with IVIG for acute relapses was conducted. IVIG was used in the majority of cases because of lack of response to steroids with/without PLEX. Improvement was noted in five of 11 (45.5%) events; the remaining had no further worsening. One patient, a 79-year-old woman, had a myocardial infarction seven days after IVIG. IVIG may have a role in treating acute NMO relapses.